Pengembangan Bahan Ajar Keterampilan Membaca Kritis Bermuatan Pesan Moral yang Bersumber Dari Cerpen Helvy Tiana Rosa Untuk Siswa Kelas X MAN 2 Padangsidimpuan - Febri Aulia Rangkuti; Eva Juliana (Jurnal Hata Poda, 2022)
This study aims to find out "The Development of Learning Materials for Critical Reading Skills Contained with Moral Messages Sourced from the Helvy Tiana Short Story There is for Class X Man 2 Padangsidimpuan Students". This study uses the R D cycle development method of Borg and Gall. The steps used in this study are data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and bulk results. The research instruments used were non-tests and tests. Research uses material experts to validate teaching materials. Data analysis techniques with descriptive analysis. The results of the development of critical reading skills teaching materials with moral messages derived from Helvy short stories There is no Rosa for students of class X Man 2 on the list included in the "Good" category. The results of the validation of the development of literature appreciation teaching materials in the material aspects of teaching materials amounting to 3, as a whole can be categorized as "Good". Based on the results of the critical reading assignment, the moral message originating from Helvy Tiana Rosa's short story for Students of class X MAN 2 Padangsidimpuan is known to be "very good". Can be seen from the results of the average score of 87 students with a value range of 81-100. Respond students and teachers as a whole about teaching materials critical reading skills charged with the moral message of the work of Helvy Tiana Rosa short stories with an average of 81.43% with a category desperately in need of teaching material.